Notary Responsibility to the Delay in Registration of Limited Liability Companies in Legal Entity Administration System (SABH) Ministry of Law and Human Rights In Accordance with Law Number 40 year 2007 concerning Limited Liability Companies - Meta Budiani; Amin Purnawan (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2018)
Limited Liability Company is an alliance of several people to conduct a business whose capital comes from shares owned by the members. Limited Liability Company in the current era is very much needed as the economic development. The method used was an empirical juridical method with descriptive analytical research specifications, while the data analysis method used was qualitative analysis. Based on the results of the research and discussion, it can be concluded that the delay in the registration of the establishment of a Limited Liability Company in the Legal Entity Administration System (SABH) of the Ministry of Law and Human Rights can be overcome by using the Confirmation deed on the previous deed of establishment. The delay in the registration of the establishment of a Limited Liability Company may be due to the delay in the process of making the Company's NPWP by its own Limited Company, or for other reasons which result in the date of registration cannot be registered with SABH and the previously purchased voucher has expired. Regarding the use of the affirmation deed, because of the previous deed of establishment had become an official and included in the notary protocol, the existence cannot be withdrawn. To avoid delays in registration, the notary should conduct socialization to clients who will carry out the process of establishing a Limited Liability Company.Keywords: Limited Liability Company; Legal Entity Administration System; Delay